Diversificação de receitas e o desempenho financeiro das cooperativas de crédito brasileiras - Laís Karlina Vieira (2016)
Credit unions, financial institutions, non-profit, can make use of the diversification strategy in their business by providing its members a broad portfolio of products and services. Diversification is presented as a way to explore new business opportunities, taking advantage of the resources available at the institution to achieve synergies, economy of scale and scope, provide additional sources of income thus boosting performance. The study on the effects of diversification in financial institutions in emerging countries, such as the Brazilian credit unions shows its relevance because of the impact that the economy of these countries generate in the global economy and also because of the importance of cooperatives as an instrument of financial inclusion. This way, this research aims to evaluate the diversification of revenues through the expansion of products and services, associated with the financial performance of Brazilian credit unions. For this research, first, a cluster analysis was performed in order to classify cooperatives as to the degree of diversification. Subsequently, there was the effect of the diversity performance of credit unions, through data models in dynamic estimated by systemic two stages GMM. We investigated 525 individual credit unions belonging to Sicoob, Sicredi and Unicred systems during the period 2009-2014, with the semi-annual information obtained from the Central Bank of Brazil (BCB). The results found in the cluster analysis showed that 56.8% of the sample credit unions were classified as highly diversified, 25.9% as moderately diversified and 17.3% as a low degree of diversification. In the model analysis, it was found that nine models, estimated proxies for performance based on feedback showed that diversification does not affect the return of credit unions. In three models, which used a proxy for the performance growth of adjusted net worth, it was possible to capture the effects of revenue diversification. For these three models, it was found that the diversification of income is positively related to the growth of adjusted shareholders' equity, indicating that diversification provides benefits to credit unions that drive the growth of adjusted shareholders' equity. These divergent results may indicate that the use of the diversification strategy by nonobjective credit unions themselves increases their remains or their returns. But it may suggest that this strategy is used to help cooperatives to fulfill their main obligations, to provide an extra source of funds and to maintain their positions in the financial market or even their survival. As for the limitations of this research, the proxies stand out for diversification and performance, since they may involve a more complex construction that addressed, and eminently quantitative analysis, which neglects qualitative aspects of the diversification and performance in credit unions. Finally, this study sought to contribute to the discussion on the effects of revenue diversification in the performance of credit unions operating in an emerging market, seeking to reduce the gap in national banking literature on the effects of diversification in the context of credit unions.